2011
DOI: 10.1111/j.1600-0447.2011.01776.x
|View full text |Cite
|
Sign up to set email alerts
|

Reason for clozapine cessation

Abstract: Future research should seek to further investigate why patients decide to be non-compliant and formulate their own decision to cease treatment, as this will facilitate strategies to promote adherence amongst these two groups that are potentially the most amenable to change.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
48
0
3

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(60 citation statements)
references
References 22 publications
9
48
0
3
Order By: Relevance
“…Underprescription of clozapine was observed since its reintroduction in the 1980s . It has been estimated that 20–30% of persons with schizophrenia present with a refractory form of illness and hence would benefit from a trial of clozapine , but the actual rate of clozapine prescription is at least ten times lower . With regard to geographical variations in clozapine use, Nielsen and collaborators found that the percentage of schizophrenia patients who received clozapine varied from 5.7% to 16.8% in 26 Danish hospitals, patients treated in university hospitals being less likely to be prescribed clozapine.…”
Section: Introductionmentioning
confidence: 99%
“…Underprescription of clozapine was observed since its reintroduction in the 1980s . It has been estimated that 20–30% of persons with schizophrenia present with a refractory form of illness and hence would benefit from a trial of clozapine , but the actual rate of clozapine prescription is at least ten times lower . With regard to geographical variations in clozapine use, Nielsen and collaborators found that the percentage of schizophrenia patients who received clozapine varied from 5.7% to 16.8% in 26 Danish hospitals, patients treated in university hospitals being less likely to be prescribed clozapine.…”
Section: Introductionmentioning
confidence: 99%
“…Refractory or treatment‐resistant schizophrenia (SZ) afflicts approximately 30% of individuals diagnosed with a SZ spectrum disorder (1–3). For these individuals, clozapine (CLZ) has long been considered the most efficacious treatment option and its usage is reserved for this group because of its high side effect burden (1, 2, 4).…”
Section: Introductionmentioning
confidence: 99%
“…However, it must be noted that the patients in Kane et al. (4) sample were highly resistant to previous antipsychotic treatments and although some patients fail to respond adequately to CLZ; CLZ remains the ‘gold standard’ treatment for refractory SZ (1–4).…”
Section: Introductionmentioning
confidence: 99%
“…This exceptional position which clozapine holds in the pharmacopeia for treatment-resistant schizophrenia necessitates that adverse events secondary to its usage are minimised and aggressively treated when they occur. This is in order to reduce morbidity and maximise adherence with clozapine, particularly since adverse effects are a frequent reason for clozapine discontinuation (Pai 2012;Taylor 2009). …”
Section: B a C K G R O U N Dmentioning
confidence: 99%